Investigation of Factors Influencing Audit Delay on Manufacturing Companies Listed on Indonesia Stock Exchange - Kampono Imam Yulianto; Cristino Gusmao; Zara Tania (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study examines the factors influencing audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Prior studies have reported inconsistent findings on the determinants of audit delay, particularly in emerging markets, highlighting a gap that this study seeks to address. The independent variables are company size, solvency, and Profitability, while audit delay is the dependent variable. This research employs secondary data derived from audited financial statements and annual reports. The sample consists of 140 firm-year observations selected using purposive sampling based on the following criteria: (1) companies consistently listed on the IDX during 2021–2024, (2) financial statements presented in Indonesian Rupiah with a fiscal year ending on December 31, and (3) availability of complete data for all variables. Multiple regression analysis is used to test the hypotheses. The results indicate that solvency and Profitability have a significant effect on audit delay (p < 0.05), whereas company size does not. These findings suggest that financial risk and firm performance play a more critical role in determining audit timeliness than organizational scale. The study provides practical implications for regulators and companies in improving the timeliness of financial reporting, particularly by paying closer attention to financial structure and performance factors that may contribute to audit delays.